2021
DOI: 10.3389/fnins.2021.702817
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Action of Resveratrol Through Adenosinergic Signaling in C6 Glioma Cells

Abstract: Gliomas are the most common and aggressive primary tumors in the central nervous system. The nucleoside adenosine is considered to be one major constituent within the tumor microenvironment. The adenosine level mainly depends on two enzymatic activities: 5′-nucleotidase (5′NT or CD73) that synthesizes adenosine from AMP, and adenosine deaminase (ADA) that converts adenosine into inosine. Adenosine activates specific G-protein coupled receptors named A1, A2A, A2B, and A3 receptors. Resveratrol, a natural polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
3
7
0
Order By: Relevance
“…It has been reported that RSV exerts apoptosis by increasing the activity of caspase-9 and caspase-3 while concurrently lowering mitochondrial membrane potential in HeLa cells ( 66 ). This is consistent with our previous report in C6 glioma cells, where acute RSV treatment increased caspase-3 activity without apoptotic bodies in nuclei but also elicited cell growth inhibition and cell cycle arrest in the G 1 phase ( 17 ). Furthermore, RSV strongly diminished proliferation and migration ability in HeLa and SH-SY5Y cell lines as reported here, in agreement with studies performed in murine prostate cancer cells ( 8 ) and HeLa human cervical cancer cells ( 13 ) suggesting that RSV exhibits its antitumoral action in several stages of carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It has been reported that RSV exerts apoptosis by increasing the activity of caspase-9 and caspase-3 while concurrently lowering mitochondrial membrane potential in HeLa cells ( 66 ). This is consistent with our previous report in C6 glioma cells, where acute RSV treatment increased caspase-3 activity without apoptotic bodies in nuclei but also elicited cell growth inhibition and cell cycle arrest in the G 1 phase ( 17 ). Furthermore, RSV strongly diminished proliferation and migration ability in HeLa and SH-SY5Y cell lines as reported here, in agreement with studies performed in murine prostate cancer cells ( 8 ) and HeLa human cervical cancer cells ( 13 ) suggesting that RSV exhibits its antitumoral action in several stages of carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously reported how RSV binds to the orthosteric site of adenosine A 2A receptors and acts as a non-selective agonist for adenosine receptors ( 16 ). Moreover, adenosine receptors, mainly A 1 and A 3 , seem to be involved, at least partially, in the antitumoral action of RSV in rat glioma C6 cells ( 17 ). Results presented herein reveal a clear modulation of different adenosine receptors’ gene expression which are not paralleled by changes in the corresponding protein level, mainly in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations